The Effects of an Intensive Training and Feedback Program on Police and Social Workers' Investigative Interviews of Children - Price, Heather L.; Roberts, Kim P. (Canadian journal of behavioural science, 2011)
In the present study, we assessed the effectiveness of an extensive training and feedback program with investigative interviewers of child victims of alleged abuse and neglect in a large Canadian city. Twelve investigative interviewers participated in a joint training initiative that lasted 8 months and involved classroom components and extensive weekly verbal and written feedback. Interviewers were significantly more likely to use open-ended prompts and elicited more information from children with open-ended prompts following training. These differences were especially prominent following a subsequent "refresher" training session. No negative effects of training were observed. Clear evidence was found of the benefits of an intensive training and feedback program across a wide variety of investigative interviews with children. Although previous research has found benefits of training with interviewers of child sexual assault victims, the current study extends these findings to a wide range of allegations and maltreatment contexts. Dans la présente étude, nous avons évalué l'efficacité d'un programme intensif d'entraînement et de rétroaction avec des interviewers-enquêteurs d'enfants victimes d'abus et de négligence dans une grande ville canadienne. Douze interviewers-enquêteurs ont participé à une initiative conjointe d'entraînement sur une période de 8 mois, comprenant des composantes en classe et des rétroactions verbales et écrites détaillées à chaque semaine. Les interviewers étaient significativement plus susceptibles d'utiliser des questions ouvertes et tentaient d'obtenir plus d'information auprès des enfants en utilisant ce type de questions après l'entraînement. Ces différences étaient particulièrement importantes après une session d'entraînement visant à rafraîchir la mémoire. Aucun effet négatif de l'entraînement n'a été observé. Les bénéfices d'un programme intensif d'entraînement avec rétroaction ont clairement été observés à travers une variété d'enquêtes par entrevue auprès d'enfants. Même si les recherches antérieures ont démontré les bénéfices de l'entraînement des interviewers d'enfants victimes d'agressions sexuelles, la présente étude montre que ceux-ci s'étendent à une foule d'allégations et contextes de maltraitance.